HUBUNGAN KEPATUHAN MINUM TABLET TAMBAH DARAH (FE) DENGAN KEJADIAN ANEMIA PADA IBU HAMIL DI WILAYAH KERJA PUSKESMAS KAYUTANGI BANJARMASIN TAHUN 2024 - Ningrum, Eva Puspita; Kirana , Rita; Kristiana , Efi; Isnaniah, Isnaniah (Seroja Husada: Jurnal Kesehatan Masyarakat, 2025)
B Background : In developing countries cases of iron deficiency anemia in pregnant women are more common in Southeast Asia including Indonesia.Based on data from Kayutangi Health Center, the percentage of pregnant women who experienced anemia increased in 2023 by 18.8% with a total of 291 pregnant women. Objective : To determine the relationship between Fe tablet consumption compliance and the incidence of anemia in pregnant women in the Kayutangi Health Center working area. Method : This research uses a correlation analytical research design using an approach method cross sectional. Using sampling technique Total Sampling with a sample of 30 respondents from third trimester pregnant women. The independent variable in the study was the compliance of pregnant women with consuming Fe tablets. The dependent variable in this study is the incidence of anemia in pregnant women. Data collection uses a questionnaire. Data analysis uses statistical tests Spaerman Rank. Results : Non-adherent as many as 25 pregnant women (83.3%) and anemia as many as 25 people (83.3%). There was a significant relationship between adherence to taking fe tablets and the incidence of anemia in pregnant women with a p-value = 0.00 (p < 0.05). Conclusion : Adherence to taking fe tablets with the incidence of anemia is a factor that has a significant relationship.